2015
DOI: 10.1021/acsnano.5b05934
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an Inorganic Interlayer on Exciton Separation in Hybrid Solar Cells

Abstract: It has been shown that in hybrid polymer–inorganic photovoltaic devices not all the photogenerated excitons dissociate at the interface immediately, but can instead exist temporarily as bound charge pairs (BCPs). Many of these BCPs do not contribute to the photocurrent, as their long lifetime as a bound species promotes various charge carrier recombination channels. Fast and efficient dissociation of BCPs is therefore considered a key challenge in improving the performance of polymer–inorganic cells. Here we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 62 publications
(137 reference statements)
0
32
0
Order By: Relevance
“…S2H). Furthermore, tetracene acts as an efficient electron-blocking layer because of the substantial difference between its lowest unoccupied molecular orbital and the conduction band of perovskite, a characteristic that could therefore diminish carrier recombination ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…S2H). Furthermore, tetracene acts as an efficient electron-blocking layer because of the substantial difference between its lowest unoccupied molecular orbital and the conduction band of perovskite, a characteristic that could therefore diminish carrier recombination ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…The need for high temperatures, specific metal films for oxidation, and complex compound precursors in these techniques, as well as challenges in reproducibility, highlight the need for new methods to reliably deposit enabling films for cost‐effective quantum devices. Recently, atmospheric pressure spatial atomic layer deposition (AP‐SALD) systems have been utilized to grow uniform films for different applications including solar cells, transistors, and light emitting diodes . AP‐SALD is a fast and scalable thin film deposition technique that can operate at atmospheric pressure in the open air (i.e., no deposition chamber).…”
Section: Introductionmentioning
confidence: 99%
“…The same group has dedicated efforts to deposit transparent conductive oxides (TCO) layers and more complex oxides for application in photovoltaic devices [51,56,84,85]. Prof. Driscoll's group was the first one to apply the SALD technique for the deposition of active layers for new-generation solar cells [52,[71][72][73][74]. For example, Muñoz-Rojas et al showed that a 15-nm thick amorphous TiO 2 layer can act as an efficient hole blocking layer in bulk heterojunction solar cells [72].…”
Section: Taking Advantage Of Saldmentioning
confidence: 99%
“…Intrinsic metal oxides HfO 2 [11] Al 2 O 3 [14-16, 19-21, 26, 31, 35-50] ZnO [18,36,39,45,46,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] SnO x [68,69] TiO 2 [14,18,[70][71][72] Cu 2 O [46,73,74] Nb 2 O 5 [71] NiO x [91] ZrO 2 [92,93] MoO x [94] Doped SALD has also been used for LEDs, in some cases to deposit active ZnO layers for polymer and hybrid perovskite-based diodes [54,76], and in another case using Al 2 O 3 as permeation barrier for flexible organic LEDs [49]. Other authors have also demonstrated the suitability of SALD for depositing barrier and encapsulation layers both on plastic and paper substrates [14,31,40,48].…”
Section: Materials Referencesmentioning
confidence: 99%